Rencana Pengembangan Jenjang Karir Perawat Klinis Di Rumah Sakit Umum Daerah Kota Dumai - Muhammad Rizul Efendi; Elfindri; Jasrida Yunita (Sistem Informasi, 2020)
Professional nurse career development in the form of career paths is a system to improve performance and professionalism, in accordance with the field of work through enhancing competencies that produce professional performance. The aim of this research was to find out the development plan for clinical nurse careers at Dumai Regional General Hospital. The research used is qualitative method. This research was conducted in August 2018. Data analysis was carried out in the form of data appearance, data verification, and matrix formation. The informants in this study amounted to 16 people who were taken based on purposive sampling.The research results obtained important themes namely; Human Resources (HR), Costs and Internship Processes are still a problem in efforts to develop clinical nurse careers. The research results obtained important themes namely; the comparison of the number of clinical assessors and nurses is not ideal, there are regulations about the number of clinical nurses who can participate in the credential process, many clinical nurses who work not according to their competence due to the impact of the length of credential process waiting time, lack of motivation of clinical nurses in following the credential process, not yet the issuance of the prescription decree, the absence of incentives for the preceptor, the lack of formulation of an increase in career level services, and the Internship process not yet implemented in the credential process. Keyword- Career, Clinical Nurse